Structure determination, mechanistic study, and safe delivery of an anti-cancer peptide - Yu, Jing (Kansas State University, 2018)
The therapeutic peptide sequence D-K₆L₉: LKLLKKLLKKLLKLL-NH₂ was developed for treating bacterial infections and solid tumors. It is effective against both conditions, because it is capable of targeting negatively charged surface domains due to its positive charge and the presence of hydrophobic units. Here, the peptide was modified with two extra amino acids (Serine and Alanine) at both, C and N terminals, resulting in SA-D-K₆L₉-AS. The sequence and structure of the modified peptide were determined by means of 2D ¹H-¹H -COSY, NOESY, and TOCSY-NMR spectroscopy. The 3D structure of the peptide in the solution phase was generated by CNS software utilizing data generated by NOE spectroscopy. This peptide was tested on the following mouse cancer cell lines: GL 26 (glioma), 4T1 (metastasizing breast cancer), NSC (neural stem cells), and pig monocytes. The LC50 values of the modified peptide were found to be 5- 10 times more active than of the original D-K₆L₉. To gain insight into its biochemical mode of action, SA-D-K₆L₉-AS tagged with a Rhodamine dye was incubated with GL 26 cancer cells. Sequential confocal imaging (every 30 seconds) revealed that the peptide interacts with cell membranes according to the carpet mechanism, and then becomes internalized into the cytoplasm in less than 5 min. and localizes in the mitochondria. This peptide is found to be toxic to neuronal stem cells and monocytes as well, showing the same mechanisms of interaction. To avoid the non-specific toxicity of the peptide for in-vivo applications, highly mesoporous silica nanoparticles (MSN) were synthesized, which served as a “container” for drug delivery. The peptide was then loaded into the MSN. MSN were further coated with a polysilazane as “gift wrap” (gatekeeper) after loading the peptide. This gatekeeper forms a shell that contains the peptide inside the MSN. While inside the MSN, the peptide shows no toxicity at 24 hours and subsequent slow release of its payload into the cytoplasm within 72 hours. This technology could be very useful for in-vivo cancer therapy by means of targeted delivery to the cancer site with appropriate surface modification of MSNs.
Keywords: Cancer; Structure; Mechanism; Drug deliveryPeptide